Proceedings of the International and Interdisciplinary Conference IMMAGINI? Brixen, Italy, 27–28 November 2017. 2017
DOI: 10.3390/proceedings1090906
|View full text |Cite
|
Sign up to set email alerts
|

Inspired by the Atmosphere. See the Invisible

Abstract: This paper is proposed to investigate procedures which can deal with graphic formalize of numeric data relating to climatic and environmental conditions. In a scientific domain characterised by prevalence of mathematical models and statistical surveys, the possibility of making images as such becomes an additional tool for morphological research of architectural solutions influenced by environmental conditions. This methodology, along with new augmented reality technology, actually, promotes new way of dealing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…This article focuses on a question that has been largely neglected: whether and how Brazilian SSC can in fact re-politicize development, by investigating Brazil's flagship project in health cooperation: the project for the implementation of an antiretroviral (ARV) factory in Mozambique, the Sociedade Moçambicana de Medicamentos (Mozambican Pharmaceutical Ltd. -henceforth SMM). Together with the ProSavannah, the SMM was Brazil's longest and most expensive programme, and received a lot of (negative and positive) attention worldwide 2 particularly as it triggered a conflict between the governments of Brazil (henceforth GoB) and Mozambique (GoM) over the principles that should shape the SMM. As such, these projects have a higher degree of symbolic power as they can define more effectively than other projects what SSC is.…”
Section: Introductionmentioning
confidence: 99%
“…This article focuses on a question that has been largely neglected: whether and how Brazilian SSC can in fact re-politicize development, by investigating Brazil's flagship project in health cooperation: the project for the implementation of an antiretroviral (ARV) factory in Mozambique, the Sociedade Moçambicana de Medicamentos (Mozambican Pharmaceutical Ltd. -henceforth SMM). Together with the ProSavannah, the SMM was Brazil's longest and most expensive programme, and received a lot of (negative and positive) attention worldwide 2 particularly as it triggered a conflict between the governments of Brazil (henceforth GoB) and Mozambique (GoM) over the principles that should shape the SMM. As such, these projects have a higher degree of symbolic power as they can define more effectively than other projects what SSC is.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, Zilsel argued, it was 'the artisans, the mariners, shipbuilders, carpenters, foundrymen, and miners (who) were, no doubt, the real pioneers of empirical observations, experimentation and causal research' (Zilsel, 2000). Zilsel's thesis was destined to exert an enormous historiographical influence; similar lines of thought are clearly visible throughout the work of succeeding generations of historians of science, such as Paolo Rossi,1 or Reijier Hooykaas, who suggested that the emancipation of the Bhurger class in the early Renaissance helped ennoble manual work, making possible the 'co-operation of artificers and scholars (which) led to a rapid development and refinement of the experimental method' (Hooykaas, 1972, p. 92). Among contemporary historians, the most recent statement of this view appears in the work of Pamela Long, who reaffirms the Zilsel thesis by arguing that the exchange of ideas between artisans and humanists in Renaissance Italy led to a wider cultural acceptance of empirical values that formed one of the important foundations upon which the new experimental sciences would develop (Long, 2011, p. 130).…”
Section: Introductionmentioning
confidence: 99%